Enhancing the flame retardancy of polyamide 6 by guanidine sulfamate‐modified carbon nanoparticles: Carbon nanotubes versus graphite oxide. (26th December 2018) - Sheng, Zhang; Jia, Guo; Yongyuan, Sun; Zhaoxia, Lv; Xiaodong, Jin; Xiaodong, Liu; Xiaoyu, Gu; Hongfei, Li; Jun, Sun
Abstract : Different carbon nanoparticles including multi‐wall carbon nanotubes (MWNT) and graphite oxide (GO) were used to prepare polyamide 6 (PA6) composites with enhanced flame retardancy by grafting guanidine sulfamate (GAS) on nanoparticles. The modified nanoparticles were compounded with PA6 by melt blending, and the flame retardancy of PA6 was evaluated by limiting oxygen index (LOI), vertical burning (UL94), and cone calorimetry tests. The results indicated that the presence of 3 wt% MWNT‐GAS could increase the LOI of PA6 composites from 22.0 to 24.1% and the addition of 3 wt% GO‐GAS can further increase the LOI value to 25.5%, the peak heat release rate values were decreased from 780.7 to 588.1 kW/m 2 (MWNT‐GAS) and 435.6 kW/m 2 (GO‐GAS). The possible mechanisms for both flame retardancy and permeation path were also discussed. These two nanoparticles can exhibit good barrier effects by the formation of protective char layers. Besides, the tensile strength of PA6/MWNT‐GAS composites reached its maximum value of 45.8 MPa while 1% MWNT‐GAS was added. POLYM. COMPOS., 40:E1884–E1892, 2019. © 2018 Society of Plastics Engineers